2010
DOI: 10.1002/ar.21186
|View full text |Cite
|
Sign up to set email alerts
|

Histological Determination of the Areas Enriched in Cholinergic Terminals and m2 and m3 Muscarinic Receptors in the Mouse Central Auditory System

Abstract: Cholinergic projections to auditory system are vital for coupling arousal with sound processing. Systematic search with in situ hybridization and immunohistochemistry indicated that the ventral nucleus of the medial geniculate body and the nucleus of the brachium of the inferior colliculus constituted cholinergic synaptic sites in the brainstem auditory system, containing a significant number of cholinergic axon terminals and m2 receptor-expressing cell bodies. Anat Rec, 293:1393Rec, 293: -1399

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the DCN, combinations of m1–4 mAChR expression have been reported ( Chen et al, 1994 ; Godfrey et al, 1998 ; Irie et al, 2006 ; Pál et al, 2009 ; Zhao and Tzounopoulos, 2011 ; He and Wang, 2014 ). For the AVCN, only the existence of the m2 and m3 subtypes of mAChRs could be shown ( Yao and Godfrey, 1995, 1996 ; Yao et al, 1996 ; Hamada et al, 2010 ). Since the m3 receptor mediates postsynaptic excitation by inhibiting potassium currents ( Brown, 2010 ; Haga, 2013 ), a phenomenon termed the M-current ( Brown and Adams, 1980 ), we hypothesize that the modulation of SBC RMP is caused by m3 mAChR activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DCN, combinations of m1–4 mAChR expression have been reported ( Chen et al, 1994 ; Godfrey et al, 1998 ; Irie et al, 2006 ; Pál et al, 2009 ; Zhao and Tzounopoulos, 2011 ; He and Wang, 2014 ). For the AVCN, only the existence of the m2 and m3 subtypes of mAChRs could be shown ( Yao and Godfrey, 1995, 1996 ; Yao et al, 1996 ; Hamada et al, 2010 ). Since the m3 receptor mediates postsynaptic excitation by inhibiting potassium currents ( Brown, 2010 ; Haga, 2013 ), a phenomenon termed the M-current ( Brown and Adams, 1980 ), we hypothesize that the modulation of SBC RMP is caused by m3 mAChR activation.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining cholinergic fibers originate in the pontomesencephalic tegmentum ( Mellott et al, 2011 ) and thus carry only indirectly stimulus-driven information. The presence of both nicotinic acetylcholine (ACh) receptors (nAChRs) and muscarinic ACh receptors (mAChRs) has been shown in VCN on a histological level ( Happe and Morley, 1998 ; Yao and Godfrey, 1999a , b ; Morley and Happe, 2000 ; Morley, 2005 ; Motts et al, 2008 ; Hamada et al, 2010 ; Mellott et al, 2011 ; Schofield et al, 2011 ). Accordingly, acetylcholine can alter the spike rates of neurons in the VCN ( Caspary et al, 1983 ), and the excitatory effects of ACh were shown for T-stellate cells of the VCN ( Fujino and Oertel, 2001 ; Oertel and Fujino, 2001 ; Bal et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since M2 receptors are mainly presynaptic (1, 13) located and inhibitory to neuronal activity, we hypothesized that dialysis of a specific M2 receptor antagonist would reduce inhibition of presynaptic release of excitatory neuromodulators and thus increase breathing. On the other hand, since M3 receptors are predominately postsynaptic (13,27), we performed additional studies to test the hypothesis that dialysis of a specific M3 receptor antagonist should decrease breathing (36). Accordingly, in the same goats used for dialysis of 50 mM atropine, we unilaterally dialyzed a specific M2 antagonist (methoctramine hydrate, 50 mM), or a specific M3 receptor antagonist (4-diphenylacetoxy-N-methylpiperidine methiodide, 5 mM) in the awake state.…”
Section: Effects Of Dialysis Of Antagonists To Receptors For Excitatory Neuromodulators In the Vrcmentioning
confidence: 99%
“…The IClc has also been noted for its comparatively high levels of the α7 nicotinic receptor subunit and high levels of acetylcholinesterase (Happe and Morley, 2004 ; Dillingham et al, 2017 ). Muscarinic receptors also stained differentially in the IC, with an expression of m2 receptors highest in the IClc and ICd and less so in the ICc (Hamada et al, 2010 ). All of this points to a diverse effect of ACh onto several different regions of IC which are known to participate in different parallel ascending auditory and multisensory pathways (Calford and Aitkin, 1983 ; Rouiller, 1997 ; Mellott et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%